Carbon molecular sieve membranes produced from carbon-forming polymer-polyvinylidene chloride copolymer blends

By blending the carbon-forming polymer with PVDC and dehydrochloride treatment, the problems of CMS membrane structure collapse and insufficient permeability were solved, and a CMS membrane with high permeability and selectivity was prepared, which was suitable for the separation of light hydrocarbon gases.

CN113453790BActive Publication Date: 2025-01-07DOW GLOBAL TECHNOLOGIES LLC
View PDF 33 Cites 0 Cited by

Patent Information

Application Number
CN202080013317.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-25
Filing Date
2020-01-15
Publication Date
2025-01-07
Estimated Expiration
2040-01-15

AI Technical Summary

Technical Problem

In the prior art, when preparing carbon molecular sieve (CMS) membranes, it is difficult to avoid structural collapse of asymmetric hollow fibers, resulting in poor permeability and difficult to effectively separate light hydrocarbon gases such as ethylene, propylene and butene.

Method used

Carbon-forming polymers are blended with polyvinylidene chloride copolymers (PVDC), and CMS films are formed by solvent molding and dehydrochloride treatment, and pyrolysis is carried out under a non-oxidizing atmosphere to prepare an improved permeability and selectivity. CMS membrane.

Benefits of technology

The structural stability and permeability of the CMS membrane are improved, and gases of similar molecular sizes can be effectively separated, such as hydrogen/ethylene and ethylene/ethane, and maintained good mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113453790B_ABST
    Figure CN113453790B_ABST
Patent Text Reader

Abstract

A carbon molecular sieve (CMS) membrane can be advantageously prepared by pyrolyzing a membrane precursor composition, the membrane precursor composition comprising a carbon-forming polymer (e.g., polyimide) blended with a polyvinylidene chloride copolymer (PVDC), the polyvinylidene chloride copolymer being a reaction product of at least 60% by weight to 97% by weight of vinylidene chloride and at least one other comonomer, and the weight ratio of the carbon-forming polymer to the polyvinylidene chloride copolymer being greater than 1:99. The membrane precursor composition can be formed by dissolving the carbon-forming polymer and the PVDC in a solvent to form a stock solution. The stock solution can, for example, be formed into an asymmetric hollow fiber. The asymmetric hollow fiber can be heated to a temperature that dehydrochlorinates the PVDC and then subsequently heated in a non-oxidizing atmosphere to carbonize the polymer of the molded membrane, thereby forming the CMS membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citation of Related Applications

[0002] This application claims priority to U.S. Provisional Patent Application No. 62 / 796,927, filed on January 25, 2019, the entire disclosure of which is hereby incorporated by reference. Technical Field

[0003] The present invention relates to polymer membranes that can be used to prepare carbon molecular sieve (CMS) membranes that can be used to separate gases. In particular, the present invention relates to a method for producing CMS membranes from a carbon-forming polymer and a polyvinylidene chloride copolymer (PVDC) blend. BRIEF DESCRIPTION OF THE DRAWINGS

[0004] Figure 1 is a scanning electron micrograph of a cross section of a portion of a polyimide-PVDC asymmetric hollow fiber of the present invention.

[0005] Figure 2 Is Figure 1 Scanning electron micrograph of a cross section of a portion of a CMS asymmetric hollow fiber formed of polyimide-PVDC asymmetric fibers.

[0006] Figure 3 is a scanning electron micrograph of a cross section of a portion of a polyimide asymmetric hollow fiber not according to the present invention.

[0007] Figure 4 Is Figure 3 Scanning electron micrograph of a cross section of a portion of an asymmetric hollow core formed of polyimide fibers in CMS. Background Art

[0008] Membranes are widely used for separation of gases and liquids, including, for example, separation of acid gases, such as separation of CO2 and H2S from natural gas, and removal of O2 from air. Gas transport through such membranes is usually modeled by an adsorption-diffusion mechanism. Currently, polymeric membranes have been well studied and widely used for gas separation due to ease of processing and low cost. However, CMS membranes have been shown to have attractive separation performance properties that exceed those of polymeric membranes.

[0009] Polyimides have been pyrolyzed under many different conditions to form CMS membranes. U.S. Patent No. 6,565,631 discloses pyrolysis under vacuum and inert gas with trace amounts of oxygen. Other patents describe methods for producing carbon membranes (both asymmetric hollow "filaments" and flat sheets) and applications in gas separation, including, for example, U.S. Patent No. 5,288,304 and European Patent No. 0459623. Steel and Koros conducted a detailed study of the effects of pyrolysis temperature, heat soak time, and polymer composition on carbon membrane properties. (KM Steel and WJ Koros, Porosity of carbon materials and its related effects on gas separation properties Research ( Investigation of Porosity of Carbon Materials and Related Effects on Gas Separation Properties ), Carbon, 41, 253 (2003); KM Steel and WJ Koros, Pyrolysis Ginseng Study on the influence of carbon number on gas separation properties of carbon materials ( An Investigation of the Effects of Pyrolysis Parameters on Gas Separation Properties of Carbon Materials) , Carbon, 43, 1843 (2005). In these studies, the membranes were produced in an air atmosphere at a pressure of 0.03 mm Hg.

[0010] The effect of pyrolysis atmosphere has been studied. Suda and Haraya disclosed the formation of CMS films under different environments. (H.Suda and K.Haraya, Gas permeation through the micropores of carbon molecular sieve membranes derived from Kapton polyimide ( Gas Permeation Through Micropores of Carbon Molecular Sieve Membranes Derived From Kapton Polyimide) , Journal of Physical Chemistry B (J.Phys.Chem.B), 101, 3988 (1997). Similarly, Geiszler and Koros disclosed the results of O2 / N2 and H2 / N2 separation using CMS fibers produced by pyrolysis of fluorinated polyimide in helium and argon. (VC Geiszler and WJ Koros, Separation properties of carbon molecular sieve membranes in polyimide pyrolysis atmosphere The impact of energy ( Effects of Polyimide Pyrolysis Atmosphere on Separation Performance of Carbon Molecular Sieve Membranes) , "Industrial Engineering Chemistry Research (Ind. Eng. Chem. Res.)", 35, 2999 (1996)).

[0011] When asymmetric hollow fiber CMS membranes are made from polyimide, which has a thin dense separation layer and a thick internal porous support structure, it is difficult to make hollow fibers without undesirable structural collapse. The structural collapse produces an undesirably thick separation layer, resulting in poor permeability to the desired permeate gas, making the fibers commercially impractical. (See L. Xu et al. Journal of Membrane Science, 380 (2011), 138-147).

[0012] To address this problem, complex methods have been described, such as in U.S. Pat. No. 9,211,504. In this patent, the application of cross-linked sol-gel silica on the inner porous wall of the polyimide is described to reduce structural collapse during pyrolysis to form a hollow fiber CMS membrane. More recently, WO / 2016 / 048612 describes a separate specific pre-oxidation of a specific polyimide (such as 6FDA / BPDA-DAM) having the stoichiometry shown in Formula 1. Formula 1 shows the chemical structure of 6FDA / BPDA-DAM, where X and Y are each 1 to provide a 1:1 ratio.

[0013]

[0014] This polyimide, after pre-oxidation, is reported to reduce structural collapse and reduce fiber sticking during and after pyrolysis.

[0015] It has also been reported that a specific polyimide called 6FDA-DAM / DABA (3:2), shown below, which is cross-linked by decarboxylation of the DABA moiety, also reduces structural collapse, but results in an undesirably low permeability to low molecular weight olefins, making them unsuitable for separation from their corresponding paraffins. (Xu, Liren, PhD dissertation, Carbon Molecular Sieve Hollow Fiber Membranes for Olefin / paraffin Separations, Georgia Tech. Univ., 2014, pp. 136-138 and 142).

[0016]

[0017] However, subsequent studies reported that cross-linking MATRIMID polyimide asymmetric hollow fibers using diamine cross-linking compounds failed to reduce the structural collapse of the separation layer of the hollow fibers. (Bhuwania, Nitesh, PhD dissertation. (2015). Engineering the Morphology of Carbon Molecular Sieve (CMS) Hollow Fiber Membranes, Georgia Institute of Technology 2015, pp. 184-187).

[0018] It would be desirable to provide a polyimide membrane or similar polymer and a method of making a polyimide or similar polymer membrane and a method for pyrolyzing a polyimide to form a CMS membrane that avoids any of the problems mentioned above. For example, it would be desirable to provide a method that does not involve any other process steps including heat treatment or treatment prior to pyrolyzing the polyimide membrane to form a carbon molecular sieve membrane. It would also be desirable that the CMS membrane does not exhibit structural collapse while still having sufficient permeability to effectively separate valuable light hydrocarbons (such as ethylene, propylene and butene) from their corresponding paraffins. Summary of the invention

[0019] A first aspect of the present invention is a film precursor composition comprising a carbon-forming polymer blended with a polyvinylidene chloride copolymer, wherein the polyvinylidene chloride copolymer is the reaction product of at least 60 wt % to 97 wt % of vinylidene chloride and at least one other comonomer, and the weight ratio of the carbon-forming polymer to the polyvinylidene chloride copolymer is greater than 1:99.

[0020] The second aspect of the present invention is a method for forming a carbon-forming polymer-polyvinylidene chloride copolymer carbon molecular sieve membrane precursor, the method comprising:

[0021] (i) dissolving a carbon-forming polymer and a polyvinylidene chloride copolymer, the polyvinylidene chloride copolymer being the reaction product of at least 60 weight percent vinylidene chloride and at least one other comonomer, and the carbon-forming polymer and the polyvinylidene chloride copolymer being present in a weight ratio of carbon-forming polymer / polyvinylidene chloride copolymer greater than 1:99, to form a stock solution of the carbon-forming polymer and the polyvinylidene chloride copolymer in a solvent;

[0022] (ii) shaping the stock solution to form a shape; and

[0023] (iii) removing the solvent to form the carbon-forming polymer-polyvinylidene chloride copolymer carbon molecular sieve membrane precursor.

[0024] The third aspect of the present invention is a method, wherein the carbon-forming polymer-polyvinylidene chloride copolymer carbon molecular sieve membrane precursor of the second aspect is heated to a dehydrochlorination temperature of 100° C. to 180° C. to form a dehydrochlorinated precursor carbon molecular sieve membrane.

[0025] The fourth aspect of the present invention is a method for forming a carbon molecular sieve membrane, which comprises heating the dehydrochlorinated precursor carbon molecular sieve membrane of the third aspect to a pyrolysis temperature of 450° C. to 1200° C. in a non-oxidizing atmosphere for at least 15 minutes to 72 hours.

[0026] Surprisingly, blending carbon-forming polymers (such as polyimides) with polyvinylidene chloride copolymers (PVDC) achieves improved carbon molecular sieve (CMS) membranes. For example, the resulting CMS membranes may have one or more advantages compared to CMS prepared from, for example, the same polyimide. Exemplary advantages include improved permeability to the desired gas, but still having good selectivity and reducing or eliminating structural collapse of the separation layer in an asymmetric membrane (e.g., an asymmetric hollow fiber), while also maintaining good mechanical strength. Even though PVDC produces much lower carbon (about 25% vs. about 50%, respectively) than polyimides, these advantages also occur. Illustratively, the precursor membrane may allow the production of a CMS membrane that has good selectivity for gas molecules of similar size (e.g., hydrogen / ethylene; ethylene / ethane; propylene / propane and butene / butane) while still having higher permeability to target permeating gas molecules (e.g., hydrogen in a gas containing hydrogen / ethylene). That is, the selectivity / permeability characteristics (productivity) are significantly improved relative to CMS asymmetric hollow fiber membranes prepared using polyimide in the absence of PVDC.

[0027] The CMS membrane of the present invention is particularly suitable for separating gas molecules with very similar molecular sizes in a gas feed, such as hydrogen / ethylene and ethylene / ethane. It can also be used to separate gases (such as oxygen) from the atmosphere or to separate gases (e.g., methane) in a natural gas feed. DETAILED DESCRIPTION

[0028] When forming the desired CMS film, the carbon-forming polymer-PVDC composition blend is generally formed by dissolving it to form a stock solution and then forming the stock solution into a desired shape as described below. The carbon-forming polymer is blended with the polyvinylidene chloride copolymer in a weight ratio greater than 1:99. Desirably, the blending weight ratio of the carbon-forming polymer to PVDC is at least 1.5 or 2:50, 25, 10 or 5.

[0029] Carbon forming polymers herein are polymers that produce a greater amount of carbon than the PVDC composition in the blend. This generally means that when heated to the pyrolysis temperature described herein under non-oxidative conditions, carbon forming polymers produce at least about 25% by weight of the starting polymer. Typically, the amount of carbon yield is at least 30%, 35%, 40% or greater than 45% to about 70%. Exemplary carbon forming polymers include polyimide, polyetherimide, polyamide, polyvinyl chloride, polyvinylidene fluoride, cellulose ester (e.g., cellulose acetate), polyacrylonitrile, polyphenylene oxide or polyphenylene ether blended with styrene or a combination thereof. Typically, carbon forming polymers have a significant amount of aromaticity, such as greater than 50% by weight aromaticity, and desirably at least 75% by weight aromaticity. Preferably, carbon forming polymers are polyimide, polyetherimide or a combination thereof, and most preferably polyimide.

[0030] Exemplary polyetherimides for forming the film precursor composition can include any known polyetherimide, such as those formed by reacting aromatic bis(ether anhydrides) and organic diamines, such as those described in U.S. Pat. Nos. 3,847,867, 3,991,004, and 4,156,597. Examples of suitable polyetherimides include ULTEM polyetherimide resins available from Sabic, Houston, TX (Saudi Basic Industries Corporation). An example of a specific polyetherimide is ULTEM 1000 resin having the following chemical formula.

[0031]

[0032] Any vinyl chloride polymer (polyvinyl chloride, "PVC"), such as those prepared by known methods, can be used as the carbon-forming polymer. For example, PVC can be prepared by bulk, solution, suspension, and dispersion (emulsion) polymerization methods, such as those described in Encyclopedia of Polymer Science, Vol. 8, "Vinyl Chloride Polymers", MW Allsop and G. Vianello, John Wiley and Sons, pp. 437-476, (2002). An example of such a method for preparing PVC is described in U.S. Pat. No. 3,862,076. Suitable commercially available PVC can be obtained from Sigma-Aldrich Inc., St. Louis, MO. Likewise, any known acrylonitrile polymer may be used, such as the acrylonitrile polymers described in Encyclopedia of Polymer Science, Vol. 1, "Acrylonitrile and Acrylonitrile Polymers", M. Wu, John Wiley & Sons, pp. 124-174, (2001). Any known polyamide may be used, such as aliphatic, semi-aromatic or aromatic polyamides, with aromatic or semi-aromatic polyamides being preferred. Examples of commercially available polyamides include those sold, for example, under the trade names ZYTEL, TECHNYL, RILSAN, RADIPOL, TROGAMID T, AMODEL, KEVLAR, NOMEX, TEIJINCONEX, TWARON and TECHNORA. Any polyvinylidene fluoride may be used, such as those known polyvinylidene fluoride described in Kirk-Othmer Encyclopedia of Chemical Technology, "Fluorine-Containing Polymers, Poly(Vinylidene Fluoride)", J. Dohany, (2000). Any known cellulose ester (such as cellulose acetate) may be used in the present invention, such as those described in Kirk-Othmer Encyclopedia of Chemical Technology, Vol. 5, "Cellulose Esters, Organic Esters", S. Gedon and R. Fengi, (2000).Any polyphenylene oxide may be used as the carbon-forming polymer, such as those known in the art, such as those described in U.S. Pat. Nos. 3,306,874; 3,306,875; 3,432,466; 3,384,619; 3,639,656; 3,642,699; 3,661,848; 3,733,299 and 4,028,341. Commercially available blends of polyphenylene oxide and styrene may be used, such as those available under the trade name NORYL from Saudi Basic Industries Corporation in Houston, Texas.

[0033] Exemplary polyimides for forming the film precursor composition may include any aromatic polyimide described in U.S. Pat. No. 4,983,191, column 2, line 65 to column 5, line 28. Other aromatic polyimides that may be used are described in U.S. Pat. Nos. 4,717,394; 4,705,540; and re 30351. In general, suitable aromatic polyimides are generally the reaction product of a dianhydride and a diamine, which is understood to proceed by forming a polyamic acid intermediate that is subsequently ring-closed by chemical and / or thermal dehydration to form a polyimide. The desired polyimide generally contains at least two different moieties derived from diamine and dianhydride monomers selected from 2,4,6-trimethyl-1,3-phenylenediamine (DAM), dimethyl-3,7-diaminodiphenyl-thiophene-5,5'-dioxide (DDBT), 3,5-diaminobenzoic acid (DABA), 5(6)-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane (DAPI), 2,3,5,6-tetramethyl-1,4-phenylenediamine (DUENE), tetramethylmethylenediamine (TMD), and 1,3-diamino-2,4-phenylenediamine (DAM). Aniline (TMMDA), 4,4'-diamino 2,2'-biphenyl disulfonic acid (BDSA); 5,5'-[2,2,2-trifluoro-1-(trifluoromethyl) ethylidene]-1,3-isobenzofurandione (6FDA), 3,3',4,4'-biphenyl tetracarboxylic acid dianhydride (BPDA), benzene tetracarboxylic acid dianhydride (PMDA), 1,4,5,8-naphthalene tetracarboxylic acid dianhydride (NTDA) and benzophenone tetracarboxylic acid dianhydride (BTDA), wherein two or more of 6FDA, BPDA and DAM are preferred. In another embodiment, the polyimide is formed from at least one of the following diamines: 2,4,6-trimethyl-1,3-phenylenediamine (DAM), 3,5-diaminobenzoic acid (DABA), 2,3,5,6-tetramethyl-1,4-phenylenediamine (Duene) or tetramethylmethylene dianiline (TMMDA).

[0034] In a particular embodiment, the polyimide is a polyimide named 6FDA / BPDA-DAM. It can be synthesized by thermal or chemical methods from a combination of three monomers: DAM; 6FDA and BPDA, each of which can be commercially obtained, for example, from Sigma-Aldrich, St. Louis, Missouri. The following chemical structure represents 6FDA / BPDA-DAM, which has the potential to adjust the ratio between X and Y to adjust the properties of the polymer. As used in the following examples, a 1:1 ratio of component X to component Y can also be abbreviated as 6FDA / BPDA (1:1)-DAM.

[0035]

[0036] A second specific polyimide embodiment designated as 6FDA-DAM does not contain BPDA such that Y in Formula 1 above is equal to zero. The following chemical structure is shown below representing the polyimide.

[0037]

[0038] A third useful polyimide is MATRIMID TM 5218 (Huntsman Advanced Materials Americas, The Woodlands, Texas), a commercially available polyimide that is a copolymer of 3,3′,4,4′-benzophenonetetracarboxylic dianhydride and 5(6)-amino-1-(4′-aminophenyl)-1,3,3-trimethylindan (BTDA-DAPI).

[0039] Typically, the molecular weight of the carbon-forming polymer (e.g., polyimide) is sufficient to form a precursor membrane composition in a stock solution that is then formed into a shape such as a hollow fiber having the necessary strength for handling and subsequent pyrolysis, but not so high that dissolution to prepare a stock solution capable of forming a hollow fiber that also contains PVDC becomes unfeasible. Illustratively, the weight average molecular weight (M) of the polyimide carbon-forming polymer is about 100 wt %. w ) is 30 to 200 kDa, but desirably has a molecular weight of 40 to 100 kDa. The polymer molecular weight can be controlled by the stoichiometry of the dianhydride to diamine monomers, the purity of the monomers, and the use of monofunctional end-capping agents such as monoamines (i.e., aniline, 3-ethynylaniline) and monoanhydrides (i.e., phthalic anhydride, succinic anhydride, maleic anhydride).

[0040] PVDC can be any useful PVDC prepared from vinylidene chloride monomer and at least one additional comonomer. Comonomers can be selected from various materials, including vinyl monomers, vinyl chloride monomers, acrylate monomers, methacrylate monomers, styrene monomers, acrylonitrile, methacrylonitrile, itaconic acid, chlorotrifluoroethylene and combinations thereof in specific embodiments. In more specific embodiments, examples of vinyl monomers include vinyl chloride, vinyl acetate, acrylonitrile and combinations thereof. More specific examples of acrylate monomers include methyl acrylate, ethyl acrylate, butyl acrylate and combinations thereof. More specific examples of methacrylate monomers include methyl methacrylate, butyl methacrylate and combinations thereof. More specific examples of styrene monomers are styrene itself.

[0041] Based on the total weight of the copolymer, the PVDC contains at least 60 wt% vinylidene chloride, and in more preferred embodiments at least 70 wt%. However, it is further desired that the PVDC contains up to 97 wt% vinylidene chloride, and thus preferably contains a minimum of at least 3 wt% comonomer or comonomer combination; more preferably 3 wt% to 40 wt%; still more preferably 3 wt% to 30 wt%; and most preferably 3 wt% to 20 wt%.

[0042] Specific embodiments of PVDC suitable for the present invention are those containing as comonomers: acrylates, such as methyl acrylate, ethyl acrylate, butyl acrylate, or combinations thereof, in an amount of 3 wt% to 20 wt%; more preferably 3.5 wt% to 15 wt%; and most preferably 4 wt% to 12 wt%, based on the weight of the PVDC as a whole. Another specific embodiment is a PVDC containing vinyl chloride in an amount of 3 wt% to 30 wt%; more preferably 7 wt% to 28 wt%; and most preferably 9 wt% to 25 wt%.

[0043] It is also preferred that the total weight average molecular weight (Mw) of the PVDC copolymer range from 10,000 to 250,000; more preferably from 50,000 to 200,000; and most preferably from 60,000 to 150,000.

[0044] The use of additives in PVDC and carbon-forming polymer-PVDC precursor films is also considered to be within the scope of the present invention. Common additives may include but are not necessarily limited to epoxidized oil stabilizers, such as epoxidized soybean oil, epoxidized linseed oil and diglycidyl ethers of bisphenol A. Also frequently used are liquid plasticizers, such as aliphatic and aromatic esters, including, for example, dibutyl sebacate, acetyl tributyl citrate, dioctyl phthalate, etc. and combinations thereof. Other commonly used additives may include lubricants, such as polyethylene wax, paraffin, oxidized polyethylene wax and combinations thereof. Lubricants may optionally be included, and may include, for example, high-density polyethylene, acrylate copolymers and silicone polymers and combinations thereof. Another group of additives that may be included is an acid scavenger, such as epoxy compounds, magnesium hydroxide, magnesium oxide, tetrasodium pyrophosphate, calcium phosphate, magnesium phosphate, DHT 4A (a synthetic hydrotalcite-like halogen scavenger available from Kyowa Chemical Industry), calcium oxide, calcium carbonate and combinations thereof. Antioxidants may also be combined, such as phenolic resins. Combinations of any or all of these types of additives may be included in the PVDC or carbon-forming polymer-PVDC blends.

[0045] Proportionally, it is preferred that the total amount of all additives does not exceed 15 wt%, and more preferably does not exceed 8 wt% or 3 wt%. However, in many applications, a combined amount of at least 2 wt% of all additives may be typical, wherein the range of use is preferably 2 wt% to 8 wt%, and more preferably 2 wt% to 3 wt%. Those skilled in the art will be aware of the use of such additives and their indications and contraindications without further guidance herein.

[0046] PVDC can be prepared by any typical or conventional polymerization method, including but not limited to bulk polymerization, suspension polymerization and emulsion polymerization, and preferably suspension polymerization or emulsion polymerization can be used. It is generally preferred to polymerize at a temperature that ensures that all PVDC components are prevented from degrading, for example, preferably 10°C to 120°C; more preferably 20°C to 100°C; and most preferably 30°C to 90°C.

[0047] In order to mix or blend carbon-forming polymer and PVDC, it is usually dissolved in a solvent and formed into a useful shape, such as a film or a hollow fiber. Illustratively, conventional procedures known in the art can be used (see, for example, U.S. Patents 5,820,659, 4,113,628, 4,378,324, 4,460,526, 4,474,662, 4,485,056, 4,512,893 and 4,717,394). Exemplary methods include co-extrusion processes, including dry-jet wet spinning processes (wherein there is an air gap between the tip of the spinning head and the coagulation or quenching bath) or wet spinning processes (with zero air gap distance), which can be used to make hollow fibers.

[0048] In order to prepare the homogeneous blend of carbon-forming polymer and PVCD, a stock solution comprising carbon-forming polymer, PVDC and solvent is used. Generally, when preparing thin film (thin film membrane), for example, when cast on a flat plate and removing solvent, a stock solution comprising a solvent for dissolving carbon-forming polymer (for example, polyimide) and PVDC is used. When preparing hollow fibers, a stock solution of a mixture of a solvent for dissolving carbon-forming polymer and PVDC and a second solvent that does not dissolve (or dissolves to a limited extent) carbon-forming polymer and PVDC but can be miscible with the solvent for dissolving carbon-forming polymer is generally used. When carbon-forming polymer is polyimide and PVDC, exemplary solvents that can be used to dissolve, for example, carbon-forming polymers include N-methyl-2-pyrrolidone (NMP), tetrahydrofuran (THF), dimethylacetamide (DMAc) and dimethylformamide (DMF). Exemplary solvents that do not dissolve polyimide and PVDC but can be miscible with the solvent that does dissolve polyimide include methanol, ethanol, water and 1-propanol.

[0049] After forming the stock solution or just forming the stock solution, the stock solution is shaped into, for example, hollow fibers as described above. After shaping, the solvent can be exchanged with other solvents (such as methanol and hexane) to prevent, for example, pore collapse, and the solvent is further removed by any convenient method, such as applying heat, vacuum, flowing gas or a combination thereof and comprising those known in the art for forming carbon-forming polymer-PVDC carbon molecular sieve membrane precursors (also referred to herein as shaped membranes).

[0050] After the solvent is removed, the formed membrane (such as a hollow fiber) can first be heated to a dehydrochlorination temperature to further stabilize the formed membrane polymer, and specifically PVDC. Heating to a dehydrochlorination temperature below the melting temperature of PVDC (usually less than about 180°C, depending on the exact composition of the PVDC) so that the PVDC in the formed membrane is dehydrochlorinated by the removal of at least 10% of the HCl. As used herein, the term "at least 10% dehydrochlorination" means that the formed membrane has been pre-treated by removing hydrochloric acid to a point where the PVDC copolymer in the formed membrane no longer melts and begins to become non-fusible. It is recognized in the art that this change in molecular dynamics begins to occur at a point of about 10% dehydrochlorination and is completed or maintained as the dehydrochlorination level increases beyond the point. This step is called dehydrochlorination because it occurs before the pyrolysis step or can be included during the pyrolysis heating to carbonize the formed membrane.

[0051] During dehydrochlorination, the temperature is preferably maintained in the range of 100°C to 180°C (i.e., with a holding temperature), more preferably 120°C to 160°C, and most preferably 130°C to 150°C. For convenience, this is preferably carried out in air, but other atmospheres, such as N2 and other inert gases or oxidizing gases (such as CO2) or combinations thereof may also or alternatively be used, as only a relatively low level of copolymer oxidation is generally expected within the overall given temperature range. The desired dehydrochlorination, i.e., the reason for the formation of the locked structure, can be achieved by exposure to a high energy radiation source, such as gamma rays, electron beams, ultraviolet light or combinations thereof. The time can vary from several minutes to 48 hours, preferably from 10 minutes to 24 hours and most preferably from 1 hour to 12 hours, as required, to reach at least a 10% dehydrochlorination point, at which the copolymer begins to become non-fusible, i.e., can no longer be melted. Depending on the temperature and time, the degree of dehydrochlorination can vary from 5% to 100%. If more visual confirmation of the onset of infusibility is desired, additional confirmation of the percent dehydrochlorination can be obtained, for example, by thermogravimetric analysis (TGA), using standard and well-known methods and equipment.

[0052] It has been found that the formation of a carbon molecular sieve (CMS) from a carbon-forming polymer-PVDC membrane precursor composition allows the formation of a CMS asymmetric hollow fiber having a wall defined by the inner and outer surfaces of the fiber, and the wall having an inner porous support region (support layer) extending from the inner surface to an outer microporous region (separation layer), and the outer microporous region (separation layer) extends from the inner porous support region to the outer surface. Surprisingly, it has been found that when a membrane precursor composition is used, structural collapse of the inner porous support region can be avoided, and the outer microporous separation layer can be tailored to be desirable thin in the absence of any pretreatment of the polymer asymmetric hollow fiber, such as described in PCT Publication WO / 2016 / 048612 or as previously described in U.S. Patent No. 9,211,504 in combination with an inorganic gel. Avoiding structural collapse can be shown as follows. If the release layer of the formed film (ie, prior to pyrolysis) is about 0.3 to about 10 microns, the corresponding CMS fiber release layer thickness may be 20, 10, 7.5, 6.25, 5.5, 4.25 or 3.0 microns or less.

[0053] In order to form a CMS membrane from a molded film, the molded film is pyrolyzed to form a CMS membrane. The molded film, which is usually an asymmetric hollow fiber, can be pyrolyzed under different inert gas purges or vacuum conditions, preferably under inert gas purge conditions for vacuum pyrolysis, preferably at low pressure (e.g., less than 0.1 mbar). U.S. Patent No. 6,565,631 and PCT Publication WO2017 / 165098 describe a suitable heating method for pyrolyzing a molded membrane hollow fiber to form a CMS hollow fiber, and the documents are each incorporated herein by reference. The pyrolysis temperature between about 450°C and about 800°C can be advantageously used. The pyrolysis temperature can be adjusted by combining the pyrolysis atmosphere to adjust the performance properties of the resulting CMS hollow fiber membrane. For example, the pyrolysis temperature can be 1000°C or higher. Optionally, the pyrolysis temperature is maintained between about 500°C and about 650°C. The pyrolysis soak time (i.e., duration at the pyrolysis temperature) can vary (and may not include a soak time), but is advantageously between about 1 hour and about 10 hours, alternatively about 2 hours to about 8 hours, alternatively about 4 hours to about 6 hours. An exemplary heating scheme may include starting with a first set point of about 70°C, then heating to a second set point of about 250°C at a rate of about 13.3 degrees Celsius per minute, then heating to a third set point of about 535°C at a rate of about 3.85 degrees Celsius per minute, and then heating to a fourth set point of about 550°C at a rate of about 0.25 degrees Celsius per minute. The fourth set point is then optionally maintained for a determined soak time. After the heating cycle is complete, the system is typically allowed to cool while still under vacuum or under a controlled atmosphere.

[0054] Typically, the outer separation layer of the hollow fiber has a thickness of up to 10% of the wall extending from the inner surface to the outer surface. The thickness of the outer separation layer is generally 0.05 microns to 25 microns, desirably 0.05 microns to 10 microns, and more desirably 0.05 to 5 microns. Herein, micropores will mean pores with a diameter <2nm; mesopores will mean 2-50nm in diameter, and macropores will mean diameters>50nm. The microstructure of the separation layer in CMS is generally characterized by microporous pores. The support layer is generally characterized by a microstructure in which the pores are microporous, macroporous, or both.

[0055] In one embodiment, the pyrolysis utilizes a controlled purge gas atmosphere during the pyrolysis, wherein a low level of oxygen is present in the inert gas. By way of example, an inert gas such as argon is used as the purge gas atmosphere. Other suitable inert gases include, but are not limited to, nitrogen, helium, or any combination thereof. By using any suitable method such as a valve, an inert gas containing a specific concentration of oxygen can be introduced into the pyrolysis atmosphere. For example, the amount of oxygen in the purge atmosphere can be less than about 50 ppm (parts per million) O2 / Ar. Alternatively, the amount of oxygen in the purge atmosphere can be less than 40 ppm O2 / Ar. Embodiments include a pyrolysis atmosphere having about 8 ppm, 7 ppm, or 4 ppm O2 / Ar.

[0056] After pyrolysis, the formed CMS film is cooled to a temperature at which no further pyrolysis occurs. Typically, this temperature is a temperature at which decomposition products are not precipitated from the precursor polymer, and may vary from polymer to polymer. Typically, the temperature is 200°C or lower, and the temperature is typically taken as 100°C, 50°C, or substantially typical ambient temperature (20 to 40°C). Cooling can be at any useful rate, such as passive cooling (e.g., turning off the power to the furnace and allowing natural cooling). Alternatively, faster cooling may be required, such as using known techniques to achieve faster cooling, such as removing insulation or using cooling fans or using water-cooled jackets.

[0057] After cooling, the CMS hollow fiber membrane can undergo further treatment, for example to make the fiber more stable or to improve the specific permeability / selectivity of a specific gas. Such additional treatment is described in U.S. Patent Publication 2018 / 0369761, which is incorporated herein by reference.

[0058] The precursor composition enables the formation of an asymmetric hollow fiber CMS membrane without the collapse of the above-mentioned structure, and enables hydrogen to be separated desirably from light hydrocarbons (e.g., olefins) or light hydrocarbon olefins from their corresponding paraffin waxes with acceptable permeability (productivity). It is not known why the CMS membrane formed by the precursor composition can achieve these specific properties, but this may be partly due to the presence of chlorine in the CMS membrane and dehydrochlorination during heating to pyrolyze the precursor membrane composition. The method generally results in a chlorine concentration of the CMS membrane being a trace amount (above the detection limit ppm) to 0.1 weight % of the carbon molecular sieve membrane. Desirably, the chlorine concentration is 10 parts per million, 20 parts, 25 parts or 50 parts to 1000ppm. The amount of chlorine can be determined by known techniques, such as neutron activation analysis.

[0059] The gas permeation properties of a membrane can be determined by gas permeation experiments. Two intrinsic properties have utility in evaluating the separation performance of a membrane material: its "permeability" (a measure of the intrinsic productivity of the membrane); and its "selectivity" (a measure of the separation efficiency of the membrane). "Permeability" is usually determined in units of barrers (1 bar = 10 -10 [cm 3 (STP)cm] / [cm 2 s cmHg]), which is based on the flux (n i ) divided by the partial pressure difference between the upstream and downstream of the membrane (Δp i ) and multiply it by the film thickness (l) to calculate.

[0060]

[0061] Another term, “permeability”, is defined herein as the productivity of an asymmetric hollow fiber membrane and is usually expressed in gas permeance units (GPU) (1 GPU = 10 -6 [cm 3 (STP)] / [cm 2 s cmHg]) measurement, which is determined by dividing the permeability by the effective membrane separation layer thickness.

[0062]

[0063] Finally, "selectivity" is defined herein as the ability of one gas to permeate through a membrane or the permeability of the same property relative to another gas. It is measured as a unitless ratio.

[0064]

[0065] In certain embodiments, the asymmetric hollow CMS membrane produced by the method enables the carbon hollow fiber CMS membrane to have a permeability of at least 5 GPU and a selectivity of at least 10 for the target gas molecules (permeate). In certain embodiments, the permeate / retentate gas molecule pair can be ethylene / ethane, propylene / propane, butene / butane, hydrogen / ethylene, carbon dioxide / methane, water / methane, oxygen / nitrogen or hydrogen sulfide / methane. Illustratively, the feed gas typically contains at least 50% permeate gas molecules (e.g., ethylene or propylene) and 25% retentate gas molecules (e.g., ethane or propane).

[0066] In a particular embodiment, the CMS membrane produced has a permeability of at least 60 GPU for hydrogen (permeate) and a selectivity for hydrogen / ethylene of at least 120. Desirably, in this embodiment, the permeability for hydrogen is at least 80, 90, or even 100 GPU. Likewise, in this embodiment, the selectivity for hydrogen / ethylene is at least 125, 130, or 135.

[0067] The CMS membrane is particularly suitable for separating gases of similar size as described above, which involves feeding a gas feed containing the desired gas molecules and at least one other gas molecule through the CMS membrane. The flow of the gas causes the first material stream to have an increased concentration of the desired gas molecules, while the second material stream has an increased concentration of another gas molecule. The method can be used to separate any of the aforementioned gas pairs, and is particularly suitable for separating ethylene from ethane or propylene from propylene. When practicing the method, the CMS membrane desirably manufactures a module including a sealable housing, the sealable housing comprising a plurality of carbon molecular sieve membranes, the plurality of carbon molecular sieve membranes comprising at least one carbon molecular sieve membrane produced by the method of the present invention, the carbon molecular sieve membrane contained in the sealable housing. The sealable housing has an inlet for introducing a gas feed composed of at least two different gas molecules; a first outlet for allowing a permeate gas stream to flow out; and a second outlet for the retentate gas stream to flow out.

[0068] Examples

[0069] Examples 1-5: Asymmetric CMS membranes

[0070] XUS32904.01 PVDC resin (The Dow Chemical Company, Midland, MI) is a PVDC copolymer containing about 4.8 wt% of methyl acrylate comonomer. XUS32904.01 resin was dissolved in tetrahydrofuran (THF) and n-methyl-2-pyrrolidone (NMP) available from Aldrich with MATRAMID 5218 polyimide (Huntsman Advanced Materials, The Woodlands, Texas) or polyvinyl chloride (PVC) (Mw of about 62,000 and Mn of about 35,000) (Sigma-Aldrich, St. Louis, Missouri, Part No. 189588) as shown in Table 1. The solvent polymer mixture was heated to about 60-80°C to accelerate polymer dissolution. The solution was cooled to room temperature before film casting. The polymer solution was poured onto a glass plate and cast using a 10 mil knife. After 10 seconds, the glass plate with the cast polymer solution was immersed in a water bath at room temperature, thereby inducing phase inversion and producing an asymmetric membrane. An asymmetric polymer membrane was obtained after about 1-3 days in water.

[0071] Table 1: Polymer blend compositions

[0072]

[0073] One inch (25.4 mm) diameter discs were cut from the asymmetric polymer membrane. Batches of 12 discs for each example were processed as follows. An initial low temperature pretreatment was performed by sandwiching the 12 discs between a 0.1 kg porous mullite honeycomb. The HCl generated in this dehydrochlorination or pretreatment step was transported through the honeycomb channels. A scrubber connected to the oven contained a 10 wt % aqueous sodium hydroxide solution to neutralize the HCl. The oven with the 12 discs was heated to 150° C. at 1° C. / min and maintained for 12 hours under 2 liters / min of flowing air. The 12 pre-treated discs were then sandwiched between identical honeycomb plates and loaded into a nitrogen purged 5.5" OD quartz tube furnace. A scrubber connected to this furnace contained a 10 wt% aqueous sodium hydroxide solution to neutralize any additional HCl released during heating to pyrolyze the dehydrochlorinated discs. The furnace was raised to a final temperature of 550°C at a ramp rate of 3°C / min and held at the final temperature for 30 minutes before cooling to room temperature (about 25°C) to form the CMS membrane. After cooling, the CMS membrane was placed in a storage box that was continuously purged with dry nitrogen at a flow rate of 5 L / min.

[0074] CMS membrane permeation test

[0075] Using impermeable aluminum tape, CMS membrane is masked on standard 25mm filter holder (Millipore#4502500, EMD Millipore Corp., Germany), leaving the permeation area of ​​​​limitation. Then apply two parts of epoxy resin (JB Weld double tube) along the interface of band and carbon membrane. At 20 ℃, the continuous feed (containing 25sccm hydrogen, 25sccm carbon dioxide, 25sccm methane, a total of 1atm equimolar mixture) and downstream He purge (2.0sccm, 1atm) mixed gas is tested. The permeate carried by He purge gas is analyzed by the GC (gas chromatograph) with TCD (thermal conductivity detector for H2 and CO2) and FID (flame ionization detector for CH4 and other hydrocarbons). The concentration in all cases is lower than 5%, so the gas flow rate in the downstream is considered to be identical with the He flow rate. Use He purge flow rate to multiply the permeate concentration measured by GC to calculate the permeate rate. The order of the tests was kept in the order of H2, CO2 and CH4. The tests were run for several hours to days until the permeate concentrations stabilized. Table 2 shows the permeation results of the triplicate tests.

[0076] The CMS membranes of Examples 4 and 5 showed high gas permeability and selectivity. The Example 4 CMS membrane with higher PVDC content showed greater permeability than the Example 5 CMS membrane with different selectivity, indicating that the amount of PVDC can be used to tailor the performance of the separation membrane for the specific gas pairs to be separated.

[0077] Table 2

[0078]

[0079] Disk # = Individual disk tests for the indicated instance.

[0080] Example 6: Blending asymmetric CMS hollow fibers

[0081] PVDC resin (XUS32904.01), MATRIMID 5218 polyimide, NMP and THF were mixed in a three-necked flask at a weight ratio of 6:18:60:16. The mixture was heated to about 80°C to accelerate the dissolution of the polymer, thereby forming a homogeneous stock solution.

[0082] The homogenized stock solution was loaded into a 500 milliliter (mL) syringe pump and degassed overnight by heating the pump to a set point temperature of 50°C to 60°C using a heating tape.

[0083] The bore fluid (85wt% NMP and 15wt% water by total bore fluid weight) was loaded into a separate 100mL syringe pump, and the stock solution and bore fluid were then coextruded through a spinning head operated at a flow rate of 180 milliliters per hour (ml / h) for the stock solution; 60 ml / h bore fluid, using 40 μm and 2 μm metal filters to filter both the bore fluid and stock fluid in the line between the delivery pump and the spinning head. The temperature was controlled at a set point temperature of 70°C using thermocouples and heating tapes placed on the spinning head, stock filter, and stock pump.

[0084] After passing through a fifteen centimeter (cm) air gap, the nascent fibers formed from the spinneret were quenched in a water bath (50° C.) and the fibers were phase separated. The fibers were collected using a 0.32 meter (M) diameter polyethylene drum through a TEFLON guide and operated at a take-up rate of 30 meters per minute (m / min).

[0085] The fiber was cut from the drum and rinsed in separate water baths at least four times over a span of 48 hours. The rinsed fiber in a glass container was solvent exchanged three times with methanol for 20 minutes and then with hexane for 20 minutes before the fiber was recovered and dried under vacuum at a set point temperature of 110° C. for one hour or at 75° C. for 3 hours.

[0086] By placing the precursor fiber on a stainless steel wire mesh plate, using stainless steel wire to bind it to the plate respectively, the hollow fiber is pyrolyzed to form a CMS membrane. The combination of the hollow fiber and the mesh plate is placed in a quartz tube placed in a tubular furnace. The polymer asymmetric hollow fiber is pretreated and pyrolyzed in the same manner as the membranes of Examples 1-5. After cooling, the carbon fiber is placed in a storage box that is continuously purged with dry nitrogen at a flow rate of 5 liters / minute. The obtained CMS asymmetric hollow fiber membrane is installed in a Swagelok module and sealed with epoxy resin at the end for permeation testing, which is carried out in the same manner as the above-mentioned membrane permeation test.

[0087] Examples 7-8: Blending Asymmetric CMS Hollow Fibers

[0088] Example 7 was prepared using the same procedure as in Example 6, except that the fibers were pretreated to a temperature of 170°C prior to pyrolysis.

[0089] Example 8 was prepared using the same procedure as in Example 6, except that no dehydrochlorination pretreatment was performed during the pyrolysis heating.

[0090] Comparative Example 1

[0091] MATRIMID 5218 polyimide, NMP and THF and ethanol (Aldrich) are mixed in a three-necked flask with a weight ratio of 26.2:53:5.9:14.9. The solution is dissolved and spun into hollow fibers using the same procedure used in Example 6. The pyrolysis step is the same as Example 8 because it is not necessary to remove any HCl. The penetration test is carried out in the same manner as Example 6.

[0092] Figure 1 is a scanning electron micrograph (SEM) of a cross section of the precursor polymer hollow fiber of Example 6. Figure 2 is a SEM of the corresponding CMS hollow fiber of Example 6, showing that the microstructure of the precursor is maintained, and the outer separation layer of the resulting CMS asymmetric hollow fiber has little or no sintering collapse. In contrast, Figure 3 is a SEM of a cross section of the precursor polymer hollow fiber of Comparative Example 1, and Figure 4 This is a SEM of a cross section of a CMS hollow fiber. Figure 3 and 4 , it is readily apparent that significant sintering and collapse of the separation layer has occurred. Essentially, the entire wall of the asymmetric hollow fiber of Comparative Example 1 is densified. In contrast, the densified skin layer of the hollow fiber of Example 6 is less than 10 microns.

[0093] The permeabilities of the five probe gases of the CMS fibers of Examples 6 to 8 were 4-40 times higher than the permeabilities of the fibers of Comparative Example 1 (Table 3). From the results, it is readily apparent that significantly higher permeability fibers were achieved using PVDC blended with polyimide while retaining good selectivity for the desired gas pairs. The gas pair selectivity of Example 6 was much higher than that of Examples 7 and 8. The only difference between 6, 7, and 8 was the maintenance of the pretreatment temperature, or its lack thereof, clearly showing that permeability and selectivity can be optimized for specific gas pairs while exhibiting much higher productivity due to the much higher permeability.

[0094] Table 3: CMS fiber permeability properties

[0095]

Claims

1. A film precursor composition comprising a carbon-forming polymer blended with a polyvinylidene chloride copolymer, the polyvinylidene chloride copolymer being the reaction product of 60 wt % to 97 wt % of vinylidene chloride and at least one other comonomer, and wherein the weight ratio of the carbon-forming polymer to the polyvinylidene chloride copolymer is at least 2:10; The carbon-forming polymer is polyimide, polyetherimide or a combination thereof.

2. The film precursor composition of claim 1, wherein the carbon-forming polymer is a polyimide.

3. The film precursor composition of claim 1, wherein the comonomer is a vinyl monomer, a vinyl chloride monomer, an acrylate monomer, a methacrylate monomer, a styrene monomer, acrylonitrile, methacrylonitrile, itaconic acid, chlorotrifluoroethylene, or a combination thereof.

4. The film precursor composition of any one of the preceding claims, wherein the vinylidene chloride is at least 70% by weight of the polyvinylidene chloride copolymer.

5. The film precursor composition of claim 2, wherein the polyimide is an aromatic polyimide that is a reaction product of a diamine and a dianhydride.

6. The film precursor composition according to claim 5, wherein the aromatic polyimide is a reaction product of at least one of the following diamines: 2,4,6-trimethyl-1,3-phenylenediamine (DAM), 3,5-diaminobenzoic acid (DABA), 2,3,5,6-tetramethyl-1,4-phenylenediamine or tetramethylmethylenedianiline (TMMDA) and at least one of the following dianhydrides: 5,5'-[2,2,2-trifluoro-1-(trifluoromethyl)ethylidene]-1,3-isobenzofurandione (6FDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTDA) and benzophenonetetracarboxylic dianhydride (BTDA).

7. A method for forming a carbon-forming polymer-polyvinylidene chloride copolymer carbon molecular sieve membrane precursor, the method comprising: (i) dissolving a carbon-forming polymer and a polyvinylidene chloride copolymer, the polyvinylidene chloride copolymer being the reaction product of at least 60 weight percent vinylidene chloride and at least one other comonomer, and the carbon-forming copolymer and the polyvinylidene chloride copolymer being present in a carbon-forming copolymer / polyvinylidene chloride copolymer weight ratio of at least 2:10 to form a stock solution of the carbon-forming copolymer and the polyvinylidene chloride copolymer in a solvent, wherein the carbon-forming polymer is a polyimide, a polyetherimide, or a combination thereof; (ii) shaping the stock solution to form a shape; and (iii) removing the solvent to form the carbon-forming polymer-polyvinylidene chloride copolymer carbon molecular sieve membrane precursor.

8. The method of claim 7, wherein the shape is an asymmetric hollow fiber.

9. The method according to claim 7 or 8, wherein the carbon-forming polymer-polyvinylidene chloride copolymer carbon molecular sieve membrane precursor is heated to a dehydrochlorination temperature of 100°C to 180°C to form a dehydrochlorinated precursor carbon molecular sieve membrane.

10. The method according to claim 9, further comprising heating the dehydrochlorination precursor carbon molecular sieve membrane to a pyrolysis temperature of 450°C to 1200°C in a non-oxidizing atmosphere for a certain time or at least 15 minutes to 72 hours.

11. The method of claim 7, wherein the carbon-forming polymer is the polyimide.

Citation Information

Patent Citations

  • Asymmetric hollow filamentary carbon membrane and process for producing same

    EP0459623A1

  • Method of making carbon molecular sieve membranes

    US20180369761A1

  • Cyclooligomerization of 1, 3-dienes

    US3290401A

  • Oxidation of phenols

    US3306874A

  • Oxidation of phenols and resulting products

    US3306875A